PENGEMBANGAN LKPD FISIKA TINGKAT SMA BERBASIS KETERAMPILAN PROSES SAINS - Herman, Herman; Aslim, Aslim (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This article is result from Research and Development (R&D) which has general objectives to produce learning tools such as physics LKPD for high school level based on scientific process. Tool development procedure follows 4-D development model up from Thiagrajan, etc. it includes with define, design, develop, and disseminate. Model/structure of LKPD produces title, question, observation, analysis, and conclusion. This model/structure is minimalizing the guide statement like on the experiment guide book (itâ€™s like with â€œcake recipeâ€). Two professionals in validation and two apprentices (physics teacher) showed that tool has been fulfilled with valid criteria. Limited experiment tool for heat and temperature matter to SMAN 15 Makassar student show that tools has been fulfilled the criteria and effective. The smoothness of LKPD usage by the teacher in studentâ€™s science process skill in problem summarize, hypothesize, apparatus identification, writing the process plot, and find the physics concept with answering the question in LKPD can be determined. The experiment result shows that tools which have been made had fulfilled the valid criteria, practice and effective until we can implement the material in a learning process. Keywords: LKPD, science process skill, physic.